A Geography of Unconventional Tourist Mobility: New Approaches and Methodologies - Irimiás, Anna Rita; Timothy, Dallen J.; Michalkó, Gábor (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Prior to the COVID-19 pandemic, tourism had permeated all spaces of experience, reaching every country, region, settlement, and corner of the globe. In recent decades, the meanings, implications, and roles of tourism have also significantly expanded. This Special Issue focuses on unconventional tourism mobilities and same-day visits, which are an important but often neglected part of the tourism system, constantly challenging both scholars and tourism industry stakeholders. Unconventional tourism is an umbrella term that covers most kinds of unregistered or unaccounted tourist mobilities (e.g., second homes, same-day visits, illegal home rentals, visiting friends and relatives, etc.), some of which might not appear to be 'tourism' but are in certain localities and under certain conditions. Given the growth of unregistered tourist flows and unaccounted leisure mobilities, there is a need in tourism studies to apply innovative research methods and to reconceptualize the meanings of tourism in different geographical and social contexts. It is expected that people's cravings for travel in the post-pandemic era will educe new spatial and temporal tourism experiences and behaviors in which unconventional tourism will play an important role. This Special Issue helps to explore unconventional tourism mobilities as described in all their forms, focusing on the geographical patterns, processes, and hidden aspects of it.